KADAR GLUKOSA DARAH PADA PASIEN CORONARY ARTERY DISEASE (CAD) DI RSUD RADEN MATTAHER JAMBI TAHUN 2021-2024 - Rohman, Umi Rofiqul Jannah; Hiratna, Hiratna; Kusdiyah, Erny (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
Coronary Artery Disease (CAD) is a condition in which the coronary arteries experience narrowing or blockage, resulting in reduced oxygen supply to the heart. In CAD patients, elevated blood glucose levels or hyperglycemia may occur, regardless of the presence of diabetes mellitus. This is due to activation of the sympathetic nervous system and increased levels of catecholamines and cortisol, which stimulate gluconeogenesis and glycogenolysis. This study aims to determine the relationship between blood glucose levels and CAD. The research design is analytical observational with a cross-sectional approach. A total of 131 samples that met the inclusion criteria were analyzed using univariate and bivariate analysis with the Chi-Square Test of Independence. The results showed that most CAD patients were male (74.8%) and aged 56–65 years (46.6%). The most common diagnosis was STEMI (42.7%), and the majority of patients had normal random blood glucose levels (63.4%). The highest mean random blood glucose level was found in STEMI patients (143.59 mg/dL), while the lowest was in UAP patients (136.68 mg/dL). Statistical analysis showed a p-value > 0.973, indicating no significant relationship between blood glucose levels and CAD. It can be concluded that there is no association between blood glucose levels and CAD diagnosis.